PENYELESAIAN PERKARA TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA MENURUT HUKUM ADAT BATAK DI TAPUNG HULU - Hartini, Theresia Devi; Efendi, Erdianto; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the Indonesian positive law, criminal matters must be resolved in court proceedings. But in Certain cases it is possible Reviews their settlement out of court, one of the which is the completion undertaken by traditional institutions items, namely through the intermediary of King parhata, as an alternative to settling Disputes in the field of criminal law in the application of customary law , such as in Sub Tapung Reviews those upstream. This study aims: Firstly; to Determine Whether the legal system Batak Recognized in the Indonesian legal system legalistic, Second; to Determine the Batak settlement in line with the nature of criminal law as public law, the Third; to Determine the legal effect of the settlement Batak.This type of research can be classified in this type of sociological juridical research, because they live in this study the authors conducted research on a study in order to provide a complete and clear picture of the issues examined. This research was conducted in the district of Hulu Tapung Kampar regency. While the overall population and sample the parties relating to the issues examined in this study, the data source used primary data, secondary data and data tertiary, data collection techniques in this study with interviews and literature study.From the research there are three main things that can be inferred. First, in the completion of the crime of domestic violence still adheres to the settlement that is familial with deliberation in reaching a decision under the provisions of customary conducted with intermediaries King parhata, remedy criminal assault domestic violence recognized in the Indonesian legal system that was legalistic. Both the completion of criminal assault domestic violence is not in line with the nature of criminal law as public law. Third, the completion of the criminal case of domestic violence according to the customary law of the Batak have legal certainty, as the settlement was made in the form of an agreement that contains several provisions which, if breached customs will be penalized in the form of customary feed local communities (parsahutaon). Advice writer, it is advisable to conduct a study and explore the local wisdom of indigenous people and a number of laws related to the existence and authority of traditional institutions in resolving a case that recognized indigenous and authority in resolving a legal issue. Second, that the King of indigenous parhata upgraded in terms of making agreements and sanctions. Third, the completion of the offense by the law should be retained in any problems that occur in the middle of the community as a form of respect and uphold the customs as the main protection.Keywords: Settlement - Crime - Customary Law